1982
DOI: 10.1128/jvi.41.1.183-191.1982
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of infection by spleen necrosis virus: inhibition in stationary cells and the role of secondary infection

Abstract: investigated by studying the kinetics of synthesis of viral DNA after secondary infection. MATERIALS AND METHODS Cells and virus. The general sources and procedures for obtaining and propagating avian fibroblast cells have been previously described (21).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…This value is in the same range of copy numbers determined previously for simian foamy virus type 3-infected cells (36). However, it is 10 to 100 times more than the amounts of unintegrated DNA reported for other retroviruses of avian, feline, and human origins (5,16,27,43).…”
Section: Resultssupporting
confidence: 79%
“…This value is in the same range of copy numbers determined previously for simian foamy virus type 3-infected cells (36). However, it is 10 to 100 times more than the amounts of unintegrated DNA reported for other retroviruses of avian, feline, and human origins (5,16,27,43).…”
Section: Resultssupporting
confidence: 79%
“…Multiple copies of unintegrated proviral DNA per cell have been demonstrated in tissue culture infections with cytopathic animal retroviruses. Examples include equine infectious anemia virus [Rasty et al, 1990], visna virus [Brahic et al, 1981], feline leukemia virus [Mullins et al, 1986], spleen necrosis virus [Chen and Temin, 1982], avian leukosis virus [Weller and Temin, 1981], and reticuloendotheliosis virus [Temin et al, 1980]. Similarly, unintegrated human immunodeficiency virus type-1 (HIV-1) proviral DNA has been demonstrated in acute in vitro infections of lymphocytes [Pauza et al, 1990;Robinson and Zinkus, 1990], monocytes [Besansky et al, 1991], and chronically infected cell lines [Chowdhury et al, 1992].…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant retroviruses are currently the vehicle of choice for the transfer of genes into mammalian cells (Anderson, 1992;Crystal, 1995;Hodgson, 1995;Miller, 1992;Mulligan, 1993). It is generally believed that cell division is a requirement for successful replication of oncoretroviruses (Bukrinsky et al, 1992;Chen and Temin, 1982;Fritsch and Temin, 1977;Harel, 1981;Roe et al, 1993;Springett et al, 1989;Varmus et al, 1977;Yoshikura, 1970), but not of lentiviruses such as HIV-1 (Bukrinsky et al, 1992;Lewis and Emerman, 1994). Studies with replication-defective retrovirus have shown that gene transfer was inhibited 100-fold in nonreplicating (confluent) vs. replicating cells (Miller et al, 1990).…”
Section: Introductionmentioning
confidence: 99%